Splitting of timber beams caused by perpendicular to grain forces of multiple connections. (15th September 2018) - Leijten, A.J.M.
Highlights: Timber beams loaded perpendicular to grain by multiple connections fail by splitting. Empirical models based on tensile stress perpendicular to grain are non-conservative. Linear fracture mechanical models are limited in predicting the splitting capacity. No models yet exist able to predict the splitting phenomenon when multiple connections are applied. An empirically determined modification factor in combination with a fracture model accounts for the non-linearity when applying multiple connections. Abstract: Beams, which are loaded perpendicular to grain by connections along the span, may fail by splitting. Empirical and semi-empirical models assume that when multiple connections are spaced more than twice the beam depth, the splitting strength of each connection is not influenced. New evidence has emerged from recent laboratory experiments, with up to five connections per beam, which proves that this assumption does not hold and results in a non-conservative estimation of the splitting capacity. Evaluation of the test data shows that a simple adjustment factor can be derived to account for multiple connections that fit well into the current Eurocode 5 fracture model.